Population Genetic Divergence among Worldwide Gene Pools of the Mediterranean Mussel Mytilus galloprovincialis - Yassine Ouagajjou; Adil Aghzar; Pablo Presa (Animals, 2023)
The Mediterranean mussel Mytilus galloprovincialis is distributed in both hemispheres either natively or introduced. The updated population genetic distribution of this species provides a useful knowledge against which future distribution shifts could be assessed. This study, performed with seven microsatellite markers and three reference species (M. edulis, M. chilensis and M. trossulus), aimed to determine the scenario of genetic divergence between 15 samples of M. galloprovincialis from 10 localities in Europe, Africa, Asia, Australia, North America and South America. In agreement with previous data, M. trossulus was the most divergent taxon of the genus, but M. chilensis appeared as an intermediate taxon between M. edulis and M. galloprovincialis, though closer to this latter. M. galloprovincialis from the Atlantic Northeast appears as the most likely source of worldwide exotic settlements instead of the previously thought Mediterranean population. The successful worldwide establishment of M. galloprovincialis suggests it is a flexible evolutionary species (FES), i.e., a species or population whose genetic background allows it to rapidly adapt to changing environments. This natural endowed plastic adaptation makes it a candidate resilient species amidst the ongoing climatic change.